Are the Japanese selfish, altruistic, or dynastic? - Charles Yuji Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2001)
In this paper, I analyze a variety of evidence for Japan and, where available, for the United States on bequest practices, on the importance and nature of bequest motives, on bequest division, on the willingness of individuals to help others, etc., in order to shed light on which model of household behavior applies in the two countries. My results suggest that the selfish life cycle model is the dominant model of household behavior in both countries but that it is far more applicable in Japan than it is in the U.S., that the dynasty model is also more applicable in Japan than it is in the U.S. but that it is not of dominant importance even in Japan, and conversely, that the altruism model is far more applicable in the U.S. than it is in Japan.
Keywords: D12; D64; D91; E21; 330; Erbe; Altruismus; Lebenszyklus; Theorie; Japan